Individualism in the Novels of Nuruddin Farah - Moolla, Fatima Fiona (Department of English Language and Literature, 2014)
The subject conceived as 'individual' is a sustained focus across the novels of Somali writer, Nuruddin Farah. This thesis locates a reading of individualism in Farah's novels in the context of the historical and philosophical development of modern identity in the societies of the North-Atlantic. It relies primarily on the analysis of philosopher, Charles Taylor, who proposes that individualism makes modern identity an historically unprecedented mode of conceiving the person. By individualism, Taylor refers to the inward location of moral sources in orientation around which the self is constituted. Nonindividualist conceptions of the self locate moral horizons external to the subject thereby defined. The novel appears to be the most significant cultural form which mutually constitutes modern subjectivity. This is suggested by the centrality of the Bildungsroman sub-genre which fundamentally determines the form of the novel. Farah's work spans the historical development of the novel from the proto-realism of his first publication, through modernism and postmodernism, returning to the 'neo-realism' of his most recent novel. The representation of the subject in the novel suggests transformations in identity which belie the uniformity of the disengaged, autonomous self which is articulated in the novel as a genre. Tension thus is generated between the social commitment Farah expresses as a writer and the limitations of the form which deny representation to the heteronomous subjectivities who are the objects of Farah's concern. The introduction identifies the centrality of individualism to Farah's project. Chapter 1 explores the historical development of individualism and genealogies of alternative conceptions of self. Chapter 2 addresses the articulation of individualism in the classic Bildungsroman, the sub-genre which defines the novel. Chapter 3 interrogates Farah's use of the 'dissensual' Bildungsroman to escape the contradiction of the classic Bildungsroman. Chapter 4 focuses on how modernism in the novels allows aesthetic resolution of individualist contradiction through fragmentation. Chapter 5 explores the resistance encountered when the novel attempts to represent heteronomy rather than autonomy. Chapter 6 suggests the indispensability of coherent subjectivity to Farah's socially committed stance. Within the philosophical matrix of individualism, the 'performative' or 'stylized' subject is the consequential form of identity.